Deciphering drivers of ICT use in agricultural education - MALIK, ANIL KUMAR; GODARA, A K; YADAV, KRISHAN; KUMAR, SUNIL; SINGH, SURYAPAL (The Indian Journal of Agricultural Sciences, 2021)
Information and Communication Technology (ICT) is an important element in the education scenario to prepare citizens for the future. Since, its inception factors influencing the use have not been studied more, hence an exploratory research study has been framed for finding those factors among the students of CCS Haryana Agricultural University, Hisar, Haryana during 2018-19. The data were collected from 200 respondents using structured interview schedule and analyzed using standard methodology. The findings revealed that the institutional factors were perceived highest with composite index value (CIV) of 70.18, followed by personal (67.35), technical (59.15) and economic constraints (47.33). Although, these factors could be overcome through implementing remedies suggested by students like; teaching should be through ICTs, followed by improved internet connection, training programme related to use of ICTs, etc. but an effective national level policy related to infrastructure facilities, software licensing, availability of high quality ICT gadgets at subsidized rates, free and regular training programmes, etc. are possible ways to deal with these factors especially during COVID-19 pandemic. The correlation and regression of different variables, i.e. age, education, family education, scientism, annual expenditure, mass media exposure, information seeking behaviour and risk orientation exhibited negative and significant effect with their perceived personal factors at 0.05 level of probability. Hence, the paper recommends that effective utilization of ICT depends not only upon the available ICT resources, but also effective utilization of the same.